Detection of mixed infections among three begomoviruses in pumpkin using multiplex polymerase chain reaction technique - Supakitthanakorn, Salit; Suksodkhiaw, Thanakit; Aupanun, Sunittra; Auvuchanon, Anyamanee (Agriculture and Natural Resources, 2024)
Importance of the Work: Begomoviruses limit pumpkin cultivation. Precise virus detection is essential for understanding disease etiology and planning disease management strategies. Objectives: To investigate multiple infections of three begomoviruses in pumpkins using multiplex polymerase chain reaction (PCR) assay. Materials and Methods: Total DNA was extracted from pumpkin leaves collected in Nakhon Pathom and Chiang Mai provinces, Thailand. ToLCNDV-, TYLCKaV- and TYLCTHV-specific primers were used to optimize the multiplex PCR amplification. Sensitivity and specificity of the multiplex PCR assay were assessed. Then, the assay was performed to investigate mixed Begomovirus infections in pumpkins. Results: The multiplex PCR assay successfully detected amplicons of ToLCNDV (400 bp), TYLCTHV (770 bp) and TYLCKaV (831 bp). The limit of detection was 1 × 10-4 diluted DNA, with no cross-reactivity among the three begomoviruses observed. The investigation of mixed infections revealed that ToLCNDV and TYLCTHV were the most frequently co-infected (76.00%), followed by multiple infections of all three begomoviruses (8.00%). Single infections of TYLCKaV, TYLCTHV and ToLCNDV were 6.00%, 4.00% and 2.00%, respectively. In summary, multiple Begomovirus infections were common in pumpkins. Main finding: Multiplex PCR assay detected mixed infections of begomoviruses in pumpkins for the first time. ToLCNDV and TYLCTHV were commonly detected together and could serve as targets for breeding resistant pumpkin cultivars to enhance disease control. Therefore, multiplex PCR could be used routinely to investigate mixed infections of begomoviruses in pumpkins.